2017
DOI: 10.3382/ps/pew461
|View full text |Cite
|
Sign up to set email alerts
|

Productive performance and blood profiles of laying hens fed Hermetia illucens larvae meal as total replacement of soybean meal from 24 to 45 weeks of age

Abstract: The aim of the research was to study the effects of an insect meal from Hermetia illucens larvae (HILM) as complete replacement of soybean meal (SBM) on productive performance and blood profiles of laying hens, from 24 to 45 wk of age. A total of 108 24-week-old Lohmann Brown Classic laying hens was equally divided into 2 groups (54 hens/group, 9 replicates of 6 hens/group). From 24 to 45 wk of age, the groups were fed 2 different isoproteic and isoenergetic diets: the control group (SBM) was fed a corn-soybea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
140
11
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 169 publications
(196 citation statements)
references
References 26 publications
25
140
11
8
Order By: Relevance
“…illucens had no negative effects on laying hen health status as reported in the same experimental design previously published 18 (Table 1). The insect meal was also able to affect some nutritional characteristics of the eggs (Table S1).…”
Section: Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…illucens had no negative effects on laying hen health status as reported in the same experimental design previously published 18 (Table 1). The insect meal was also able to affect some nutritional characteristics of the eggs (Table S1).…”
Section: Resultssupporting
confidence: 76%
“…(2017) 18 was probably promoted by increased of satiety. It has been suggested that SCFAs, derived from bacterial fermentation of dietary fibers, stimulate the production and secretion of satiety-related hormones associated with fed or fasted state (GLP-1 and PYY) 46 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations